PERENCANAAN FASILITAS PENGELOLAAN SAMPAH BERKELANJUTAN: DESAIN TPS3R UNTUK KAMPUS UNIVERSITAS PALANGKA RAYA - Perdian, Alprido; Lendra, Lendra; Faqih, Nasyiin (Fakultas Teknik dan Ilmu Komputer (FASTIKOM) UNSIQ, 2025)
The growth of the academic community at Palangka Raya University has led to significant waste problems. Without an appropriate and sustainable management system, the accumulation of waste can have a negative impact on environmental cleanliness, the health of the campus community, and the aesthetics and image of the institution. To address these challenges, a more progressive and sustainability-oriented waste management system is needed through the planning and construction of a Reduce, Reuse, Recycle Waste Management Facility (TPS3R). This planning includes building design and the preparation of a Cost Estimate Plan (RAB) tailored to the needs of Palangka Raya University. The implementation of the construction project requires comprehensive and accurate budget calculations. The preparation of the cost plan must consider the principle of economic efficiency while maintaining consistency with established quality standards and technical specifications. Based on the analysis conducted by the researchers, waste generation data was obtained, and the TPS3R building design for Palangka Raya University is planned to cover an area of 216 square metres with a budget plan of Rp 752,964,900.00. It is hoped that the design planning of the TPS3R building at Palangka Raya University will not only serve as a technical solution to waste management issues but also as a model for campus environmental management that can be replicated in other educational institutions.